Radiation cooling ceramic colorant and preparation method and application thereof

CN122917570APending Publication Date: 2026-10-16南宁桂电电子科技研究院有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611097226.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]本发明的目的在于提供一种辐射制冷陶瓷色料及其制备方法与应用,旨在解决现有技术中提出现有的,在辐射制冷陶瓷色料使用过程中,其应用到建筑屋顶和建筑外墙,其通过高效反射太阳光和高发射中红外波实现被动降温的陶瓷基功能色料,也就是辐射制冷降温,可是,辐射制冷陶瓷色料应用在室外,其室外空气会含有灰尘,进而附着在辐射制冷陶瓷色料上,容易影响辐射降温的效率,进而大大降低了辐射制冷陶瓷色料的应用的问题

Benefits of technology

本发明的辐射制冷陶瓷色料通过SiO2-Al2O3-ZrO2共晶粉体、锐钛矿型纳米TiO2、烧结助剂Li2CO3、堇青石粉体、氟硅烷改性纳米SiO2、锐钛矿纳米TiO2和γ-氨丙基三乙氧基硅烷(KH550)之间的配合,将氟硅烷改性纳米SiO2、锐钛矿纳米TiO2和γ-氨丙基三乙氧基硅烷(KH550)制备成抗积尘功能预混粉,然后加入SiO2-Al2O3-ZrO2共晶粉体、锐钛矿型纳米TiO2、烧结助剂Li2CO3和堇青石粉体当中,进而形成的辐射制冷陶瓷色料可以有效减少灰尘附着,减少灰尘对辐射制冷陶瓷色料的辐射制冷降温影响。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917570A_ABST
    Figure CN122917570A_ABST
Patent Text Reader

Abstract

This invention belongs to the field of building technology, specifically relating to a radiation-cooled ceramic colorant and its preparation method and application, including SiO2-Al2O3-ZrO2 eutectic powder, anatase nano-TiO2, sintering aid Li2CO3, cordierite powder, fluorosilane-modified nano-SiO2, anatase nano-TiO2 and γ-aminopropyltriethoxysilane (KH550). The radiation-cooled ceramic colorant of the present invention is prepared by combining SiO2-Al2O3-ZrO2 eutectic powder, anatase nano-TiO2, sintering aid Li2CO3, cordierite powder, fluorosilane-modified nano-SiO2, anatase nano-TiO2, and γ-aminopropyltriethoxysilane (KH550) to form an anti-dust-accumulation premixed powder. This premixed powder is then added to the SiO2-Al2O3-ZrO2 eutectic powder, anatase nano-TiO2, sintering aid Li2CO3, and cordierite powder. The resulting radiation-cooled ceramic colorant can effectively reduce dust adhesion and reduce the impact of dust on the radiation-cooled ceramic colorant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of building technology, specifically relating to a radiation-cooled ceramic colorant, its preparation method, and its application. Background Technology

[0002] Radiation-cooled ceramic pigments are ceramic-based functional pigments that achieve passive cooling by efficiently reflecting sunlight and emitting mid-infrared waves without consuming additional energy. They combine decorative appeal with radiation-cooling performance, making them suitable for the energy-saving and aesthetic needs of buildings, roads, and other applications.

[0003] In the application of radiation-cooled ceramic pigments to building roofs and exterior walls, these ceramic-based functional pigments achieve passive cooling by efficiently reflecting sunlight and emitting mid-infrared waves. However, when used outdoors, the outdoor air contains dust, which adheres to the pigments and affects their cooling efficiency, thus significantly reducing their application. Summary of the Invention

[0004] The purpose of this invention is to provide a radiation-cooled ceramic pigment, its preparation method, and its application. This invention aims to address the problem that existing radiation-cooled ceramic pigments, when used on building roofs and exterior walls, achieve passive cooling through efficient reflection of sunlight and high emission of mid-infrared waves. However, when applied outdoors, dust in the outdoor air adheres to the pigment, affecting its cooling efficiency and significantly reducing its application potential.

[0005] To achieve the above objectives, the present invention provides the following technical solution: a radiation-cooled ceramic colorant, comprising: SiO2-Al2O3-ZrO2 eutectic powder, anatase nano-TiO2, sintering aid Li2CO3, cordierite powder, fluorosilane-modified nano-SiO2, anatase nano-TiO2, and γ-aminopropyltriethoxysilane (KH550), wherein the ratio is 70%:22%:3%:5%:3%:4%:0.5%, wherein the Si... The O2-Al2O3-ZrO2 eutectic powder has a particle size of 1-3 μm, the anatase nano-TiO2 has a particle size of 20-30 nm, the sintering aid Li2CO3 is analytical grade, the cordierite powder has a particle size of 5-10 μm, the fluorosilane modified nano-SiO2 has a particle size of 30 nm and a surface energy of <23 mN / m, the anatase nano-TiO2 has a particle size of 15-20 nm, and the γ-aminopropyltriethoxysilane (KH550) is industrial grade.

[0006] As a preferred embodiment of the radiation-cooled ceramic colorant of the present invention, the SiO2-Al2O3-ZrO2 eutectic powder is composed of a eutectic structure powder formed by three oxides: silicon dioxide (SiO2), aluminum oxide (Al2O3), and zirconium dioxide (ZrO2), with a ratio of 59.5%:25.5%:15%.

[0007] As a preferred embodiment of the radiation-cooled ceramic colorant of the present invention, during the synthesis of the SiO2-Al2O3-ZrO2 eutectic powder, silicon dioxide (SiO2), aluminum oxide (Al2O3), and zirconium dioxide (ZrO2) are added to a planetary ball mill according to the specified ratio. Subsequently, 0.5%-1% of the sintering aid Li2CO3 is added, using anhydrous ethanol as the medium, at a ratio of total powder mass to anhydrous ethanol volume of 1 kg: 1.2-1.5 L, with a ball-to-powder ratio of 4:1 and a rotation speed of 3000 rpm. The powder was ball-milled at 0 r / min for 4 h to ensure uniform mixing and fine particle size. The ball-milled slurry was then dried in an oven at 80℃ for 3 to 4 h. After grinding, the powder was passed through a 200-mesh sieve to obtain a uniformly mixed powder. The powder was then placed in an alumina crucible and placed in a box furnace. Under an air atmosphere, the heating rate was 5℃ / min, the calcination temperature was 1280-1320℃, and the holding time was 3-4 h. At high temperature, the three oxides underwent a solid-state reaction to form a SiO2-Al2O3-ZrO2 eutectic structure.

[0008] A method for preparing radiation-cooled ceramic pigments includes the following steps: S1, fluorosilane-modified nano-SiO2, anatase nano-TiO2, and γ-aminopropyltriethoxysilane (KH550) are mixed according to a certain ratio, anhydrous ethanol is added and ultrasonically dispersed for 30 min, dried at 60℃, and then ground to obtain a premixed powder with anti-dust accumulation function; S2, SiO2-Al2O3-ZrO2 eutectic powder, anatase nano-TiO2, sintering aid Li2CO3, and cordierite powder are placed in a planetary ball mill, using anhydrous ethanol as the medium and agate balls as the grinding medium (ball-to-material ratio 3:1), and the rotation speed is... Ball milling at 300 r / min for 2 h, then add anti-dust premixed powder and continue ball milling for 1 h. The ball milling slurry is spray dried (inlet air temperature 180℃, outlet air temperature 80℃) to obtain particles with a particle size of 80-150 μm. S3, The particles are loaded into an alumina crucible and placed in a roller kiln. Under an air atmosphere with an oxygen volume fraction ≥20%, the temperature is increased to 1180℃ at 5℃ / min and held for 2 h. The furnace is then cooled to room temperature. S4, The sintered blocks are coarsely crushed by a jaw crusher and finely crushed by an air jet mill. The sintered blocks are then passed through a 325 mesh sieve to obtain eutectic powder with a particle size of 1-3 μm.

[0009] In a preferred embodiment of the method for preparing radiation-cooled ceramic pigments according to the present invention, in step S1, fluorosilane-modified nano-SiO2, anatase nano-TiO2, and γ-aminopropyltriethoxysilane (KH550) are mixed in a ratio of 3g:4g:0.5g, with a total powder mass of 7.5g, and added at a ratio of total powder mass: anhydrous ethanol volume = 1g:3-4mL.

[0010] In a preferred embodiment of the radiation-cooled ceramic pigment preparation method of the present invention, in step S1, the proportioned materials are placed in a container and then placed in an ultrasonic cleaner. The ultrasonic cleaner uses a frequency of 40kHz and a power of 200W for 30 minutes of ultrasonic cleaning. During the process, the machine can be stopped and stirred 1-2 times at intervals. The high-frequency vibration will break the van der Waals forces between the powders, so that the nanoparticles are uniformly dispersed in the ethanol medium. At the same time, γ-aminopropyltriethoxysilane (KH550) will be pre-adsorbed on the particle surface, laying the foundation for subsequent interfacial compatibility. The ultrasonically cleaned slurry is transferred to an evaporating dish and placed in a forced-air drying oven at a temperature of 60℃ for drying. Drying at 60℃ can accelerate the evaporation of ethanol and prevent the powder from agglomerating due to high temperature. It takes 2-4 hours. The dried powder is then dry-milled in a planetary ball mill for 5-10 minutes, and then passed through a 200-300 mesh standard sieve to remove a small amount of undispersed powder agglomerates, finally obtaining a uniform particle size anti-dust premixed powder.

[0011] In a preferred embodiment of the method for preparing radiation-cooled ceramic pigments according to the present invention, in step S2, the slurry after ball milling is adjusted to a solid content of 30%-40% before being spray-dried. 0.5%-1% polyvinyl alcohol (PVA) can be added as a binder to improve the strength of the granulated particles. The mixed slurry is pumped into the atomizer of the spray dryer by a high-pressure pump, and then the atomized droplets are sent into the drying tower to obtain particles with a particle size of 80-150μm. The atomizer is a centrifugal atomizer with a rotation speed of 10000-20000r / min; or a pressure nozzle with a nozzle orifice diameter of 0.5-1.0mm and a working pressure of 2-5MPa.

[0012] In a preferred embodiment of the radiation-cooled ceramic colorant preparation method of the present invention, in step S3, the particles are uniformly and uncompactedly laid in an alumina crucible with a particle thickness of 5-10 mm. During the cooling stage, an air atmosphere is maintained, and the temperature is first cooled to 500°C at a rate of 5°C / min, and then cooled to room temperature at a rate of 10°C / min.

[0013] In a preferred embodiment of the method for preparing radiation-cooled ceramic pigments according to the present invention, in step S4, the feeding rate of both the jaw crusher and the air jet mill is 20-30 kg / h, the classifying wheel speed of the air jet mill is 18000-22000 r / min, the vibration frequency during sieving is 100-120 Hz, and the sieving time is ≥15 min.

[0014] As a preferred application of the radiation-cooled ceramic pigment of the present invention, the radiation-cooled ceramic pigment is used in the field of construction.

[0015] Compared with the prior art, the beneficial effects of the present invention are: The radiation-cooled ceramic colorant of the present invention is prepared by combining SiO2-Al2O3-ZrO2 eutectic powder, anatase nano-TiO2, sintering aid Li2CO3, cordierite powder, fluorosilane-modified nano-SiO2, anatase nano-TiO2, and γ-aminopropyltriethoxysilane (KH550) to form an anti-dust-accumulation premixed powder. This premixed powder is then added to the SiO2-Al2O3-ZrO2 eutectic powder, anatase nano-TiO2, sintering aid Li2CO3, and cordierite powder. The resulting radiation-cooled ceramic colorant can effectively reduce dust adhesion and reduce the impact of dust on the radiation-cooled ceramic colorant.

[0016] The method for preparing radiation-cooled ceramic colorants of this invention, through a combination of ball milling, spray drying, drying, pulverizing and sieving, can achieve control over particle morphology and size, providing uniform raw materials for subsequent sintering. Attached Figure Description

[0017] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings: Figure 1 This is a schematic diagram of the structure of the radiation-cooled ceramic colorant preparation method of the present invention; Figure 2 This is a schematic diagram of the structure of the method for preparing the anti-dust-accumulation functional premixed powder of the present invention; Figure 3 This is a schematic diagram of the structure of the radiation-cooled ceramic colorant preparation equipment of the present invention. Detailed Implementation

[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0019] Example 1 Please see Figures 1-3This invention provides the following technical solution: a radiation-cooled ceramic colorant, comprising: SiO2-Al2O3-ZrO2 eutectic powder, anatase nano-TiO2, sintering aid Li2CO3, cordierite powder, fluorosilane-modified nano-SiO2, anatase nano-TiO2, and γ-aminopropyltriethoxysilane (KH550), wherein the ratio is 70%:22%:3%:5%:3%:4%:0.5%, wherein the SiO2- The Al2O3-ZrO2 eutectic powder has a particle size of 1-3 μm, the anatase nano-TiO2 has a particle size of 20-30 nm, the sintering aid Li2CO3 is analytical grade, the cordierite powder has a particle size of 5-10 μm, the fluorosilane modified nano-SiO2 has a particle size of 30 nm and a surface energy of <23 mN / m, the anatase nano-TiO2 has a particle size of 15-20 nm, and the γ-aminopropyltriethoxysilane (KH550) is industrial grade.

[0020] Preferably, the SiO2-Al2O3-ZrO2 eutectic powder is composed of a eutectic structure powder formed by three oxides: silicon dioxide (SiO2), aluminum oxide (Al2O3), and zirconium dioxide (ZrO2), with a ratio of 59.5%:25.5%:15%.

[0021] Preferably, in the synthesis of the SiO2-Al2O3-ZrO2 eutectic powder, silicon dioxide (SiO2), aluminum oxide (Al2O3), and zirconium dioxide (ZrO2) are added to a planetary ball mill according to the specified ratio. Then, 0.5%-1% of the sintering aid Li2CO3 is added. Anhydrous ethanol is used as the medium, and the powder is added at a ratio of total powder mass to anhydrous ethanol volume of 1 kg: 1.2-1.5 L. The ball-to-powder ratio is 4:1, and the mill speed is 300 r / min. Grind for 4 hours to ensure uniform powder mixing and fine particle size. Then, dry the ball-milled slurry in an oven at 80℃ for 3 to 4 hours. After grinding, pass through a 200-mesh sieve to obtain uniformly mixed powder. Place the powder into an alumina crucible and put it in a box furnace. Under air atmosphere, the heating rate is 5℃ / min, the calcination temperature is 1280-1320℃, and the holding time is 3-4 hours. At high temperature, the three oxides undergo a solid-state reaction to form a SiO2-Al2O3-ZrO2 eutectic structure.

[0022] In this embodiment, the radiation-cooled ceramic colorant is prepared by first preparing SiO2-Al2O3-ZrO2 eutectic powder according to the corresponding ratio, and then feeding it into a planetary ball mill. Next, sintering aid Li2CO3 and anhydrous ethanol are added, and then the planetary ball mill starts working with a ball-to-powder ratio of 4:1, a rotation speed of 300 r / min, and ball milling for 4 hours to ensure that the powder is mixed evenly and the particle size is fine. Then, the ball mill slurry is placed in a container and dried in an 80°C oven for 3 to 4 hours. Then, it is fed into a pulverizing device, pulverized, and then fed into a sieving device. After sieving, a uniformly mixed powder is obtained. Then, the powder is loaded into an alumina crucible, and then the three oxides undergo a solid-phase reaction at high temperature to form a SiO2-Al2O3-ZrO2 eutectic structure.

[0023] It is worth noting that SiO2-Al2O3-ZrO2 eutectic powder can also be purchased directly from ceramic raw material suppliers and customized with specific requirements for eutectic structure, particle size and ZrO2 content.

[0024] Further noteworthy points are: the sintering aid Li2CO3 can optimize the eutectic structure at a low calcination temperature, while silicon dioxide (SiO2) forms a silicon-aluminum eutectic matrix, improving weather resistance; aluminum oxide (Al2O3) and silicon dioxide (SiO2) form a eutectic, enhancing infrared emissivity; and zirconium dioxide (ZrO2) is the core high infrared emission component, meeting the requirements of the 8-13μm band.

[0025] Example 2 A method for preparing radiation-cooled ceramic pigments includes the following steps: S1, mixing fluorosilane-modified nano-SiO2, anatase nano-TiO2, and γ-aminopropyltriethoxysilane (KH550) according to a specified ratio, adding anhydrous ethanol, ultrasonically dispersing for 30 min, drying at 60℃, and then grinding to obtain an anti-dust-accumulation premixed powder; S2, placing SiO2-Al2O3-ZrO2 eutectic powder, anatase nano-TiO2, sintering aid Li2CO3, and cordierite powder into a planetary ball mill, using anhydrous ethanol as the medium and agate balls as the grinding medium (ball-to-material ratio 3:1), at a speed of 300 rpm. Ball milling at r / min for 2 hours, then adding anti-dust premixed powder and continuing ball milling for 1 hour. The ball milling slurry is spray dried (inlet air temperature 180℃, outlet air temperature 80℃) to obtain particles with a particle size of 80-150μm. S3. The particles are loaded into an alumina crucible and placed in a roller kiln. Under an air atmosphere with an oxygen volume fraction ≥20%, the temperature is increased to 1180℃ at 5℃ / min and held for 2 hours. The furnace is then cooled to room temperature. S4. The sintered blocks are coarsely crushed by a jaw crusher and finely crushed by an air jet mill. The sintered blocks are then passed through a 325-mesh sieve to obtain radiation-cooled ceramic colorant powder with a particle size of 1-3μm.

[0026] Preferred: In step S1, fluorosilane-modified nano-SiO2, anatase nano-TiO2 and γ-aminopropyltriethoxysilane (KH550) are mixed in a ratio of 3g:4g:0.5g, with a total powder mass of 7.5g, and added at a ratio of total powder mass: anhydrous ethanol volume = 1g:3-4mL.

[0027] Preferred method: In step S1, the proportioned materials are placed in a container and then placed in an ultrasonic cleaner. The ultrasonic cleaner uses a frequency of 40kHz and a power of 200W for 30 minutes of ultrasonic cleaning. During the process, the machine can be stopped and stirred 1-2 times at intervals. The high-frequency vibration will break the van der Waals forces between the powders, so that the nanoparticles are uniformly dispersed in the ethanol medium. At the same time, γ-aminopropyltriethoxysilane (KH550) will be pre-adsorbed on the particle surface, laying the foundation for subsequent interfacial compatibility. The ultrasonic slurry is transferred to an evaporating dish and placed in a forced-air drying oven. The temperature is set to 60℃ for drying. Drying at 60℃ can accelerate the evaporation of ethanol and prevent the powder from agglomerating due to high temperature. It takes 2-4 hours. The dried powder is dry-milled in a planetary ball mill for 5-10 minutes, and then passed through a 200-300 mesh standard sieve to remove a small amount of undispersed powder agglomerates. Finally, a premixed powder with uniform particle size and anti-dust accumulation function is obtained.

[0028] Preferably, in step S2, the slurry after ball milling is adjusted to a solid content of 30%-40% before spray drying. 0.5%-1% polyvinyl alcohol (PVA) can be added as a binder to improve the strength of the granulated particles. The mixed slurry is pumped into the atomizer of the spray dryer by a high-pressure pump, and then the atomized droplets are sent into the drying tower to obtain particles with a particle size of 80-150μm. The atomizer is a centrifugal atomizer with a rotation speed of 10000-20000r / min; or a pressure nozzle with a nozzle orifice diameter of 0.5-1.0mm and a working pressure of 2-5MPa.

[0029] Preferably, in step S3, the particles are uniformly and uncompactedly laid in the alumina crucible with a particle thickness of 5-10 mm. During the cooling stage, an air atmosphere is maintained, and the temperature is first cooled to 500°C at a rate of 5°C / min, and then cooled to room temperature at a rate of 10°C / min.

[0030] Preferably, in step S4, the feeding rate of both the jaw crusher and the air jet mill is 20-30 kg / h, the classifying wheel speed of the air jet mill is 18000-22000 r / min, the vibration frequency during screening is 100-120 Hz, and the screening time is ≥15 min.

[0031] In this embodiment, fluorosilane-modified nano-SiO2, anatase nano-TiO2, and γ-aminopropyltriethoxysilane (KH550) were mixed in a specific ratio. The mixed material was placed in a container and then placed in an ultrasonic cleaner. The ultrasonic cleaner used a frequency of 40kHz and a power of 200W for 30 minutes, with the machine stopped and stirred 1-2 times during the process. The high-frequency vibration broke the van der Waals forces between the powder particles, allowing the nanoparticles to be uniformly dispersed in the ethanol medium. At the same time, γ-aminopropyltriethoxysilane (KH550) pre-adsorbed on the particle surface, laying the foundation for subsequent interfacial compatibility. The ultrasonically treated slurry was transferred to an evaporating dish and placed in a forced-air drying oven at 60℃. Drying at 60℃ can accelerate ethanol evaporation and prevent powder agglomeration due to high temperature. This process takes 2-4 hours. After drying, the powder was dry-milled in a planetary ball mill for 5-10 minutes, and then passed through a 200-300 mesh standard sieve to remove a small amount of undispersed material. The powder agglomerates were processed to obtain a uniformly sized, anti-dust-accumulation functional premixed powder. Subsequently, SiO2-Al2O3-ZrO2 eutectic powder, anatase nano-TiO2, sintering aid Li2CO3, and cordierite powder were placed in a planetary ball mill. Anhydrous ethanol was used as the grinding medium, and agate balls were used as the grinding media (ball-to-material ratio 3:1). The milling speed was 300 r / min for 2 hours. Then, the anti-dust-accumulation functional premixed powder was added, and milling continued for another hour. The milled slurry was then spray-dried. (Inlet air temperature 180℃, outlet air temperature 80℃) to obtain particles with a particle size of 80-150μm. Then, the particles are loaded into an alumina crucible and placed in a roller kiln. Under an air atmosphere with an oxygen volume fraction ≥20%, the temperature is increased to 1180℃ at 5℃ / min and held for 2 hours. The furnace is then cooled to room temperature. Subsequently, the sintered blocks are coarsely crushed by a jaw crusher and finely crushed by an air jet mill, and then passed through a 325-mesh sieve to obtain radiation-cooled ceramic colorants with a particle size of 1-3μm.

[0032] It is worth noting that: Anatase nano-TiO2: directly mixed mechanically with eutectic powder, during sintering, some anatase nano-TiO2 particles will adhere to the surface of the eutectic grains, while the other part will be embedded in the grain boundaries, which not only achieves white coloring but also enhances solar spectral reflectivity; Sintering aid Li2CO3: It is mixed in a molecular-level dispersion form and decomposes into Li2O at high temperature, which reduces the sintering temperature of the eutectic powder, promotes the densification of the matrix, and does not form an independent crystalline phase. Cordierite powder: As an inert dispersed phase, it fills the grain boundaries of the eutectic matrix, inhibits excessive growth of eutectic grains at high temperatures, and maintains the microstructure stability of the pigment. Fluorosilane-modified nano-SiO2 and anatase nano-TiO2: Pre-modified with γ-aminopropyltriethoxysilane (KH550) to improve interfacial compatibility with the eutectic matrix, and uniformly dispersed in the matrix after mixing; after sintering, fluorosilane-modified nano-SiO2 will be enriched on the pigment surface to form a low surface energy layer, while anatase nano-TiO2 will be dispersed in the matrix and surface, playing a photocatalytic self-cleaning role; γ-aminopropyltriethoxysilane (KH550): As a surface modifier, it reduces the agglomeration between different powders. It is not a coating layer, but rather acts as a "bridge" to improve the uniformity of the mixed system.

[0033] An application of a radiation-cooled ceramic pigment, wherein the radiation-cooled ceramic pigment is used in the construction field.

[0034] Working principle: First, fluorosilane-modified nano-SiO2, anatase nano-TiO2, and γ-aminopropyltriethoxysilane (KH550) are prepared to obtain an anti-dust-accumulation premixed powder. Then, silicon dioxide (SiO2), aluminum oxide (Al2O3), and zirconium dioxide (ZrO2) are prepared into a SiO2-Al2O3-ZrO2 eutectic powder. Next, the SiO2-Al2O3-ZrO2 eutectic powder, anatase nano-TiO2, sintering aid Li2CO3, and cordierite powder are placed in a planetary ball mill. Anhydrous ethanol is used as the grinding medium, and agate balls are used as the grinding media (ball-to-material ratio 3:1). The milling speed is 300 r / min for 2 hours. Finally, the anti-dust-accumulation premixed powder is added. The functional premixed powder was ball-milled for another 1 hour. The ball-milled slurry was spray-dried (inlet air temperature 180℃, outlet air temperature 80℃) to obtain particles with a particle size of 80-150μm. The particles were then loaded into an alumina crucible and placed in a roller kiln. Under an air atmosphere with an oxygen volume fraction ≥20%, the temperature was increased to 1180℃ at a rate of 5℃ / min and held for 2 hours. The kiln was then cooled to room temperature. The sintered blocks were coarsely crushed by a jaw crusher and finely crushed by an air jet mill. The sintered blocks were then passed through a 325-mesh sieve to obtain radiation-cooled ceramic pigment powder with a particle size of 1-3μm. In use, the radiation-cooled ceramic pigment powder can effectively reduce dust adhesion and reduce the impact of dust on the radiation-cooled ceramic pigment's cooling effect, with a dust reduction rate of 75%.

[0035] Finally, it should be noted that the above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A radiation-cooled ceramic colorant, characterized in that, include: The mixture comprises SiO2-Al2O3-ZrO2 eutectic powder, anatase nano-TiO2, sintering aid Li2CO3, cordierite powder, fluorosilane-modified nano-SiO2, anatase nano-TiO2, and γ-aminopropyltriethoxysilane (KH550), wherein the ratio is 70%:22%:3%:5%:3%:4%:0.5%. The SiO2-Al2O3-ZrO2 eutectic powder has a particle size of 1-3 μm, the anatase nano TiO2 has a particle size of 20-30 nm, the sintering aid Li2CO3 is analytical grade, the cordierite powder has a particle size of 5-10 μm, the fluorosilane modified nano SiO2 has a particle size of 30 nm and a surface energy of <23 mN / m, the anatase nano TiO2 has a particle size of 15-20 nm, and the γ-aminopropyltriethoxysilane (KH550) is industrial grade.

2. The radiation-cooled ceramic colorant according to claim 1, characterized in that: The SiO2-Al2O3-ZrO2 eutectic powder is composed of a eutectic structure powder formed by three oxides: silicon dioxide (SiO2), aluminum oxide (Al2O3), and zirconium dioxide (ZrO2), with a ratio of 59.5%:25.5%:15%.

3. The radiation-cooled ceramic colorant according to claim 2, characterized in that: In the synthesis of the SiO2-Al2O3-ZrO2 eutectic powder, silicon dioxide (SiO2), aluminum oxide (Al2O3), and zirconium dioxide (ZrO2) are added to a planetary ball mill according to the specified ratio. Then, 0.5%-1% of the sintering aid Li2CO3 is added. Anhydrous ethanol is used as the medium, and the powder is added at a ratio of total powder mass to anhydrous ethanol volume of 1 kg: 1.2-1.5 L. The ball-to-powder ratio is 4:1, the milling speed is 300 r / min, and the milling process is repeated 4 times. h, to ensure uniform powder mixing and fine particle size, the ball mill slurry is then dried in an oven at 80℃ for 3 to 4 hours. After grinding, it is passed through a 200-mesh sieve to obtain uniformly mixed powder. The powder is then placed in an alumina crucible and placed in a box furnace. Under air atmosphere, the heating rate is 5℃ / min, the calcination temperature is 1280-1320℃, and the holding time is 3-4 hours. At high temperature, the three oxides undergo a solid-state reaction to form a SiO2-Al2O3-ZrO2 eutectic structure.

4. A method for preparing radiation-cooled ceramic colorant according to any one of claims 1-3, characterized in that, Includes the following steps: S1. Fluorosilane-modified nano-SiO2, anatase nano-TiO2 and γ-aminopropyltriethoxysilane (KH550) are mixed in proportion, anhydrous ethanol is added and ultrasonically dispersed for 30 min, dried at 60℃ and then ground to obtain anti-dust premixed powder. S2. SiO2-Al2O3-ZrO2 eutectic powder, anatase nano-TiO2, sintering aid Li2CO3, and cordierite powder are placed in a planetary ball mill. Anhydrous ethanol is used as the medium, and agate balls are used as the grinding medium (ball-to-material ratio 3:1). The milling speed is 300 r / min, and the milling time is 2 h. Then, anti-dust premixed powder is added, and the milling continues for 1 h. The milled slurry is spray-dried (inlet air temperature 180℃, outlet air temperature 80℃) to obtain particles with a particle size of 80-150 μm. S3. The particles are loaded into an alumina crucible and placed in a roller kiln. Under an air atmosphere with an oxygen volume fraction ≥20%, the temperature is increased to 1180℃ at 5℃ / min, held for 2 hours, and then cooled to room temperature with the furnace. S4. The sintered block is coarsely crushed by a jaw crusher and finely crushed by an air jet mill, and then passed through a 325-mesh sieve to obtain eutectic powder with a particle size of 1-3μm.

5. The method for preparing radiation-cooled ceramic colorant according to claim 4, characterized in that: In step S1, fluorosilane-modified nano-SiO2, anatase nano-TiO2 and γ-aminopropyltriethoxysilane (KH550) are mixed in a ratio of 3g:4g:0.5g, with a total powder mass of 7.5g, and added at a ratio of total powder mass: anhydrous ethanol volume = 1g:3-4mL.

6. The method for preparing radiation-cooled ceramic colorant according to claim 4, characterized in that: In step S1, the prepared materials are placed in a container and then placed in an ultrasonic cleaner. The ultrasonic cleaner uses a frequency of 40kHz and a power of 200W for 30 minutes of ultrasonic cleaning. During the process, the machine can be stopped and stirred 1-2 times at intervals. The high-frequency vibration will break the van der Waals forces between the powders, so that the nanoparticles are uniformly dispersed in the ethanol medium. At the same time, γ-aminopropyltriethoxysilane (KH550) will be pre-adsorbed on the particle surface, laying the foundation for subsequent interfacial compatibility. The ultrasonic slurry is transferred to an evaporating dish and placed in a forced-air drying oven at a temperature of 60℃ for drying. Drying at 60℃ can accelerate the evaporation of ethanol and prevent the powder from agglomerating due to high temperature. It takes 2-4 hours. After drying, the powder is dry-milled in a planetary ball mill for 5-10 minutes, and then passed through a 200-300 mesh standard sieve to remove a small amount of undispersed powder agglomerates, finally obtaining a uniform particle size anti-dust premixed powder.

7. The method for preparing radiation-cooled ceramic colorant according to claim 4, characterized in that: In step S2, the slurry after ball milling is adjusted to a solid content of 30%-40% before spray drying. 0.5%-1% polyvinyl alcohol (PVA) can be added as a binder to improve the strength of the granulated particles. The mixed slurry is pumped into the atomizer of the spray dryer by a high-pressure pump, and then the atomized droplets are sent into the drying tower to obtain particles with a diameter of 80-150μm. The atomizer is a centrifugal atomizer with a rotation speed of 10000-20000r / min; or a pressure nozzle with a nozzle orifice diameter of 0.5-1.0mm and a working pressure of 2-5MPa.

8. The method for preparing radiation-cooled ceramic colorant according to claim 4, characterized in that: In step S3, the particles are evenly and uncompactedly laid in the alumina crucible with a particle thickness of 5-10 mm. During the cooling stage, an air atmosphere is maintained, and the temperature is first cooled to 500°C at a rate of 5°C / min, and then cooled to room temperature at a rate of 10°C / min.

9. The method for preparing radiation-cooled ceramic colorant according to claim 4, characterized in that: In step S4, the feeding rate of both the jaw crusher and the air jet mill is 20-30 kg / h, the classifying wheel speed of the air jet mill is 18000-22000 r / min, the vibration frequency during screening is 100-120 Hz, and the screening time is ≥15 min.

10. A radiation-cooled ceramic colorant according to any one of claims 1-3, characterized in that: Application of radiation-cooled ceramic colorants in the construction field.